Measurements of the elastic and anelastic properties of sandstone flooded with supercritical CO2 - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (Wiley-Blackwell, 2014)
The aim of this study was to investigate the effects of supercritical CO2 (scCO2) injection on the elastic and anelastic properties of sandstone at seismic and ultrasonic frequencies. We present the results of the low-frequency and ultrasonic experiments conducted on water-saturated sandstone (Donnybrook, Western Australia) flooded with scCO2. The sandstone was cut in the direction perpendicular to a formation bedding plane and tested in a Hoek triaxial pressure cell. During the experiments with scCO2, the low-frequency and ultrasonic systems and the pump dispensing scCO2 were held at a temperature of 42°C. The elastic parameters obtained for the sandstone with scCO2 at seismic (0.1 Hz–100 Hz) and ultrasonic (~0.5 MHz) frequencies are very close to those for the dry rock. The extensional attenuation was also measured at seismic frequencies for the dry, water-saturated, and scCO2-injected sandstones. The applicability of Gassmann's fluid substitution theory to obtained results was also tested during the experiments.